A three‐tier framework for monitoring antiretroviral therapy in high HIV burden settings - Meg Osler; Katherine Hilderbrand; Claudine Hennessey; Juanita Arendse; Eric Goemaere; Nathan Ford; Andrew Boulle (Journal of the International AIDS Society, 2014)
The provision of antiretroviral therapy (ART) in low and middle‐income countries is a chronic disease intervention of unprecedented magnitude and is the dominant health systems challenge for high‐burden countries, many of which rank among the poorest in the world. Substantial external investment, together with the requirement for service evolution to adapt to changing needs, including the constant shift to earlier ART initiation, makes outcome monitoring and reporting particularly important. However, there is growing concern at the inability of many high‐burden countries to report on the outcomes of patients who have been in care for various durations, or even the number of patients in care at a particular point in time. In many instances, countries can only report on the number of patients ever started on ART. Despite paper register systems coming under increasing strain, the evolution from paper directly to complex electronic medical record solutions is not viable in many contexts. Implementing a bridging solution, such as a simple offline electronic version of the paper register, can be a pragmatic alternative. This paper describes and recommends a three‐tiered monitoring approach in low‐ and middle‐income countries based on the experience implementing such a system in the Western Cape province of South Africa. A three‐tier approach allows Ministries of Health to strategically implement one of the tiers in each facility offering ART services. Each tier produces the same nationally required monthly enrolment and quarterly cohort reports so that outputs from the three tiers can be aggregated into a single database at any level of the health system. The choice of tier is based on context and resources at the time of implementation. As resources and infrastructure improve, more facilities will transition to the next highest and more technologically sophisticated tier. Implementing a three‐tier monitoring system at country level for pre‐antiretroviral wellness, ART, tuberculosis and mother and child health services can be an efficient approach to ensuring system‐wide harmonization and accurate monitoring of services, including long term retention in care, during the scale‐up of electronic monitoring solutions.